Nutritional ingredients and prevention of chronic diseases by fermented koumiss: a comprehensive review - Xue, Weikang; Yuan, Xiaoxia; Ji, Zhaojun; Li, Hua; Yao, Yitong (Frontiers in Nutrition, 2023)
Koumiss, a traditional fermented dairy product made from fresh mare milk, is a sour beverage that contains an abundance of microbial communities, including lactic acid bacteria, yeast and others. Firstly, probiotics such as Lacticaseibacillus in koumiss can induce the secretion of immunoglobulin G in serum and interleukin-2 in the spleen while beneficial Saccharomyces can secrete antibacterial compounds such as citric acid and ascorbic acid for specific immunopotentiation. Additionally, more isoflavone in koumiss can regulate estrogen levels by binding to its receptors to prevent breast cancer directly.Bile salts can be converted into bile acids such as taurine or glycine by lactic acid bacteria to lower cholesterol levels in vivo. Butyric acid secretion would be increased to improve chronic gastrotis by regulating intestinal flora with lactic acid bacteria. Finally, SCFA and lCFA produced by Lacticaseibacillus inhibit the reproduction of pathogenic microorganisms for diarrhea prevention. Therefore, exploring the mechanisms underlying multiple physiological functions through utilizing microbial resources in koumiss represents promising avenues for ameliorating chronic diseases.